Perception of illness among patients with heart failure is related to their general health independently of their mood and functional capacity - Anners Lerdal (Journal of Patient-Reported Outcomes, 2019)
Abstract Purpose To explore the relationship between illness perceptions and self-reported general health of patients with chronic heart disease, using some core elements from the Common Sense Model. Methods Patients with heart failure (New York Heart Association [NYHA] Functional Class I-III) from five outpatient clinics in Eastern Norway were invited to participate in this cross-sectional study. Two research nurses collected socio-demographic data (age, sex, education and work status) and standardized questionnaires in structured interviews. Patients’ self-reported general health was measured with the Euro-Qual Visual Analogue Scale (EQ-VAS), illness perceptions were measured with the 8-item Brief Illness Perception Questionnaire (BIPQ), and mood was assessed using the Hospital Anxiety and Depression Scale. Results Among the 220 patients who were recruited into this study (98% response rate), the mean age was 67.5 years (SD ± 12.5), and 65.9% were men. Patients were classified as NYHA Class I (8.7% with no activity limitations), Class II (47.6% with slight limitations), or Class III (43.8% with marked limitations). Mean EQ-VAS score was 58.8 (SD ± 21.0). Three of the eight perception of illness items (consequences, personal control and identity) were associated with the patients’ general health rating, controlling for their NYHA Class, mood and other BIPQ items. Conclusions Our findings suggest that patients’ perceptions of their illness have an independent and substantial relationship to the self-rated general health of patients with chronic heart failure. Peoples’ illness perceptions are beliefs that have been shown to be modifiable in clinical interventions. Thus, targeted interventions aimed to modify these, such as patient education courses, ought to be developed and tested, as they may be helpful for improving perceived health status.